Analisis Evaluasi Pembelajaran Aqidah Akhlak Dalam Sistem Kredit Semester Di Madrasah Tsanawiyah Cerdas Istimewa Amanatul Ummah - M Husnur Rofiq; Nuril Ainun Nadliroh (FATAWA: Jurnal Pendidikan Agama Islam, 2022)
Evaluation is a tool that can measure success in the learning process, while SKS (Semester Credit System) is one of the programs in education where students determine their own learning load. This purpose of article is: (1) How is the Semester Credit System (SKS) learning on Aqidah Morals Learning at Madrasah Tsanawiyah Cerdas Istimewa (CI) Amanatul Ummah. (2) How to carry out Aqidah Morals learning evaluation in the SKS at Amanatul Ummah's Tsanawiyah Madrasah. This study used a qualitative type of field research method. The method of collecting the data were interviews, field observations, and documentation. Data analysis techniques included data collection, data presentation, and data verification. The result of this article is, 1) Learning Semester Credit System (SKS) in Aqidah Morals Learning, were: a) Based on the 2013 curriculum b) Students need to be able to complete UKBM material in one semester for approximately 3 months. c) Using the lecture method, question and answer, and discussion. d) Develop RPP and syllabus. e) There were morning apples like istighosah activities by asking Allah for help by reading Yasin Letter. 2) However, the Aqidah Morals Learning Evaluation in the SKS, were: a) There were 3 elements of assessment like Cognitive/Knowledge, Affective, and Psychomotor/Skills. b) Daily Test Assessment, UAS/Final Test assessment, Oral and Written Assessment. e) UKBM (Independent Learning Activity Unit) Assessment. f) There was a Dhaurah/Repetition System. Keywords: Learning Evaluation, Aqidah Morals, Semester Credit System (SKS)